2011
DOI: 10.3354/meps08909
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of productivity in naturally structured macroalgal assemblages: importance of canopy structure on light-use efficiency

Abstract: Macroalgae are undoubtedly a major supplier of organic carbon to marine food webs, yet few studies have attempted to examine primary production in complex macroalgal communities. Many studies have tested the photosynthetic characteristics of single species with little attention given to the associated algal assemblages. The role of canopy structure and species diversity in these assemblages will help in understanding the role of biodiversity in enhancing ecosystem function. In the present study, photosynthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 43 publications
4
55
1
Order By: Relevance
“…37 . On the contrary, Tait and Schiel (2011) demonstrated that the structural 54 differences of primary producers, but also their location in the community assemblage could 55 lead to an enhancement of the global primary production. Therefore, all these interactions 56 play a fundamental role and need to be accounted for when investigating community 57 metabolism, as highlighted by Migné et al (2015a).…”
mentioning
confidence: 99%
“…37 . On the contrary, Tait and Schiel (2011) demonstrated that the structural 54 differences of primary producers, but also their location in the community assemblage could 55 lead to an enhancement of the global primary production. Therefore, all these interactions 56 play a fundamental role and need to be accounted for when investigating community 57 metabolism, as highlighted by Migné et al (2015a).…”
mentioning
confidence: 99%
“…(1) did not model the data at either low or high PFDs. A similar response was recorded for a mixed-canopy of Cysto phora tortulosa and Hormosira banksii, in which case P max was not achieved at PFDs of 2000 µmol photons m -2 s -1 (Tait & Schiel 2011); those authors were also unable to apply 'traditional' P vs. E models to their data. The explanation for these trends is that when growing in canopies, seaweeds self-shade: while the uppermost blades in a canopy may reach P max , or even exhibit photoinhibition, the lower blades will receive much less light and exhibit un-saturated rates of photosynthesis (Middelboe & Binzer 2004).…”
Section: Discussionmentioning
confidence: 57%
“…m -2 for Xiphophora was not seen at 41 ind. m -2 , but it is possible that if we had used higher PFDs we may have observed a pattern similar to Tait & Schiel (2011) and to that for the 13 ind. m -2 treatment in this study.…”
Section: P-e Curves and Photosynthetic Parametersmentioning
confidence: 86%
“…Although individual photosynthesis must influence the community response, individual metabolism was not expected to be closely related to community metabolism, because this represents a complex integrated response of many different species exposed to a wide range of local light conditions within the canopies (Middelboe and Binzer, 2004;Binzer and Middelboe, 2005;Middelboe et al, 2006). Tait and Schiel (2011) showed that layering within macroalgal assemblages plays a major role in maintaining net photosynthesis throughout the natural range of irradiance and even enhances photosynthesis at high irradiance. Tait and Schiel (2010) measured the underwater productivity of three fucoid assemblages.…”
Section: Variation In the Trends Of Photosynthetic Performance Accordmentioning
confidence: 99%
“…Johnson et al, 1974;Quadir et al, 1979;Dring and Brown, 1982). Since then, differences between some shallow-water macroalgae species have been shown to be smaller at the communities scale than experiments on single thallus pieces suggested (Binzer and Middelboe, 2005) and an increasing productivity of fucoid assemblages down a shore-height gradient has been shown (Tait and Schiel, 2011). These community-scale measurements were limited, however, to immerged conditions and trends might be different under peculiar conditions of the emersion periods.…”
Section: Introductionmentioning
confidence: 99%